Gambaran Variasi Menu dan Cita Rasa Makanan terhadap Kepuasan Makan Siswi di Asrama MAN 3 Palembang - Wiyanti, Sri; Andini, Andini; Podojoyo, Podojoyo; Rotua, Manuntun (JGK: Jurnal Gizi dan Kesehatan, 2023)
Satisfaction is a person's level of feeling after comparing perceived performance or results (performance received and perceived performance) with their expectations. The purpose of this study was to find out the description of menu variations and food tastes on students' eating satisfaction at MAN 3 Palembang dormitory. This research was conducted in May 2023, the number of samples was 71 people. This type of research is descriptive with a cross sectional design. Data collection used a questionnaire with univariate and bivariate data results. The results of univariate analysis showed that 61 female students (85.9%) had menu variations in the non-variable category, 58 female students (81.7%) Food Color in the attractive category, 69 female students (97.2%) Food Portion in the good category, 58 female students (81.7%) Food Aroma is in the good category, 52 female students (73.2%) Food Temperature is in the good category, 71 female students (100%) Maturity Level is in the good category, 64 Food Seasonings are in the delicious category female students (90.1%).This proves that the variety of menus at MAN 3 Palembang Dormitory is not good. It is hoped that the food processor can provide a variety of food variations, so that the level of satisfaction can meet nutritional intake